2015
DOI: 10.1002/2015gb005096
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and predictability of multiyear ecosystem variability in the North Pacific

Abstract: Aleutian Low variations provide vorticity, buoyancy, and heat-flux forcing to the North Pacific Ocean, which in turn cause changes in ocean circulation, mixed layer characteristics and sea ice coverage. In this process the white noise atmospheric characteristics are integrated dynamically and thermodynamically to generate red noise ocean spectra. Using the Community Earth System Model (version 1.0.3) we study the resulting biogeochemical and ecosystem responses in the North Pacific. We find that ocean dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 86 publications
3
10
0
Order By: Relevance
“…The potential for long‐term predictability of temperature, salinity, and nutrients associated with the propagation of subsurface anomalies along the North Pacific gyre has been identified in previous observational and modeling studies [ Chikamoto et al , ; Rykaczewski and Dunne , ; Sasaki et al , ; Taguchi and Schneider , ]. Here we show that salinity anomalies, and its subsurface propagation dynamics from the North Pacific gyre into the CCS region, lead to a skillful reconstructions of the observed multidecadal changes in CCS oxygen (Figure ).…”
Section: Discussion and Implications For Decadal Predictability Of Oxsupporting
confidence: 75%
See 1 more Smart Citation
“…The potential for long‐term predictability of temperature, salinity, and nutrients associated with the propagation of subsurface anomalies along the North Pacific gyre has been identified in previous observational and modeling studies [ Chikamoto et al , ; Rykaczewski and Dunne , ; Sasaki et al , ; Taguchi and Schneider , ]. Here we show that salinity anomalies, and its subsurface propagation dynamics from the North Pacific gyre into the CCS region, lead to a skillful reconstructions of the observed multidecadal changes in CCS oxygen (Figure ).…”
Section: Discussion and Implications For Decadal Predictability Of Oxsupporting
confidence: 75%
“…In the thermocline, large‐scale horizontal circulation plays an important role in modulating the variability of subsurface water properties in the eastern North Pacific [ Chikamoto et al , ; Kilpatrick et al , ], Gulf of Alaska [ Pozo Buil and Di Lorenzo , ], and CCS [ Bograd et al , ; Peterson et al , ]. Zonal subsurface advection from the North Pacific gyre into the CCS draws young water masses characterized by high oxygen (Figure c) and low nutrient concentration [ Hickey , ; Lynn and Simpson , ].…”
Section: Introductionmentioning
confidence: 99%
“…Though not explored in the present analysis, additional potential sources of predictability especially at long lead times include reemergence of subsurface SST anomalies when the mixed layer deepens in winter (Alexander et al 1999) and eastward advection of offshore anomalies into the CCS (Chikamoto et al 2015;Stock et al 2015). The presence of similar patterns of predictability among NMME models suggests that the skill-generating mechanisms may be the same, though captured more faithfully in some models than in others.…”
Section: Sst Forecast Skill In the Ccsmentioning
confidence: 80%
“…Whereas PDO predictive skill is contaminated by many high-frequency atmosphere-ocean phenomena (Schneider and Cornuelle 2005;Mochizuki et al 2014), our model experiments suggest that the longterm memory of NPGO is mainly attributed to lowfrequency ocean dynamics in the North Pacific. Because of the strong connection between the NPGO and marine nutrient variations (Di Lorenzo et al 2008), our successful NPGO prediction could be beneficial for marine ecosystem predictions (M. Chikamoto et al 2015). However, our findings are inconsistent with Lienert and Doblas-Reyes (2013), who suggested that the long-term SST trend is the main contributor to the NPGO predictive skills, whereas the benefits of initialization are limited to two years lead.…”
Section: Discussionmentioning
confidence: 99%
“…Skillful forecasts on multiyear to decadal time scales using a dynamical climate prediction system have potential to provide useful information for sectors such as agriculture, renewable energy, water resources, coastal Denotes content that is immediately available upon publication as open access. communities, forestry, and fisheries (Meehl et al 2014;Meehl and Teng 2014;M. Chikamoto et al 2015;Y.…”
Section: Introductionmentioning
confidence: 99%